2019
DOI: 10.15282/ijame.16.4.2019.15.0549
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of CNT/MoS2 Hybrid Nanofluid in Machining for Surface Roughness

Abstract: Present work is motivated by the high thermal conductivity of MWCNT and low coefficient of friction due to MoS2 nanoparticles which can significantly improve the heat transfer and lubrication performance of hybrid nanofluids than nanofluids. Hybrid nanofluids are prepared with CNT/MoS2 nanoparticles of 1wt% in sesame oil, neem oil and mahua oil by varying hybrid ratio (i.e. 1: 1; 1:2 and 2:1) and surfactant. The hybrid nanofluid composition is evaluated based on stability analysis from sedimentation and zeta p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These layers will slide with minimal force applied proportional to each other, thereby gaining themselves low drag properties. Of this purpose, graphite and MoS2 have used in industrial applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…These layers will slide with minimal force applied proportional to each other, thereby gaining themselves low drag properties. Of this purpose, graphite and MoS2 have used in industrial applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…More related compounds include polytetrafluoroethylene (PTU), calcium fluoride (CaF), and cerium tungsten disulfide (CeW12), have the same effect [13]. The interface of MoS 2 appears to be linear with lamella directed in the direction of motion, serving as a pathway for relative motion but hindering interaction through different sliding components under varying strain [14]. Using lubricants is useful to keep materials from adhering to each other, due to a weak bond with the surface.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that viscosity index has been increased by 5.39%, 6.71%, and 7.04% for 0.1%, 0.4%, and 0.7 wt% MoS 2 nanoparticles respectively. Some other investigations (Gugulothu and Pasam 2019, Khan et al 2020a, Nadeem et al 2021 have also been added to examine the thermophysical properties with various base fluids and hybridized with other nanoparticles. Based on the better outcomes of the CMC-based nanofluids, kerosene-based nanofluids, and MoS 2 nanoparticles, the present model is deliberated to examine the thermophysical and rheological effects on peristaltic pumping in the presence of electroosmosis.…”
Section: Introductionmentioning
confidence: 99%